Dinamika Literasi Digital Guru Kelas dalam Mengintegrasikan Teknologi Dalam Pembelajaran - Siti Arnanda Makalalag; Siti Savira Pontoh; Warraihan Musbihin R.H.D; Julfikar Kadir; Febrianti Ayuba; Fitriyanti Suleman (STAI AL-AMIN, 2026)
This research is motivated by the importance of digital literacy of classroom teachers in supporting the integration of technology in learning in elementary schools. Technological developments require teachers not only to be able to use digital devices technically, but also to integrate them pedagogically so that learning becomes more effective, interesting, and in accordance with the needs of students. In the context of SD Negeri 12 Bintauna, the use of technology in learning has been carried out, but it still shows differences in the level of mastery, form of utilization, and readiness of teachers. This study aims to examine the dynamics of digital literacy of classroom teachers in integrating technology in learning at SD Negeri 12 Bintauna and identify the forms of technology integration carried out by classroom teachers in the learning process. This study uses a qualitative approach with a descriptive type. Data was collected through observation, interviews, and documentation, then analyzed with stages of data reduction, data presentation, and conclusion drawn. The results of the study show that the digital literacy of classroom teachers is dynamic and develops gradually, but not evenly. Technology is used to find teaching materials, present materials, use visual and video media, communicate, and develop learning administration. It was concluded that technology integration has taken place, but it still needs continuous reinforcement to be more pedagogical, interactive, and student-centered.